Optimizing long-term athletic development: what practitioners know and do - Eisenmann, J. C.; Burton, A. M.; Cowburn, I.; Till, K. (Strength and Conditioning Journal, 2026)
Despite the widely recognized importance of long-term athletic development (LTAD) by scholars and practitioners who work with youth in a physical activity setting (e.g., physical education, sports, strength and conditioning, sport coaches, program directors), there is a gap between research and real-world application. In this study, we aim to address this gap by better understanding what practitioners who work with youth know and do in relation to applying LTAD, specifically developing motor skill competency. In this narrative review, we summarize three studies from our research group that evaluated the knowledge, practices, and challenges of practitioners responsible for developing motor skill competency and implementing LTAD programs. Overall, practitioners reported that it is important to develop a broad range of motor skills; however, physical education teachers did not emphasize resistance training movements until puberty. Practitioners recognized their responsibility to enhance health, fitness, and physical performance and reduce the risk of injury. However, the ability of practitioners to define athleticism and LTAD along with their familiarity with existing models was variable. Practitioners reported good adherence toward delivering LTAD programs, in spite of a range of challenges. Overall, continued mutual collaboration is warranted between scholars and practitioners related to education, knowledge translation, and implementation toward LTAD and motor skill competency.